2020
DOI: 10.1016/j.chbr.2020.100029
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 pandemic affected the susceptibility to cyberbullying in India?

Abstract: Owing to the COVID-19 induced lockdown in India, most people’s internet activity surged, leading to an expected increase in the rate of cybercrimes. This research focuses on analyzing whether the factors significant in cyberbullying susceptibility changed with the lockdown. The study was conducted by surveying 256 students before the pandemic, in October 2019, and 118 students during the lockdown, in June 2020. This included questions about the respondents’ demographics, online presence, experience with offlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 29 publications
2
69
0
5
Order By: Relevance
“…Victims of bullying are found to internalize their problems, they tend to have poor social skills, a tendency to isolate themselves [18], have low self-esteem, frustration, suicidal thoughts [17,[20][21][22], and report greater defenselessness [23]. According to different studies, cyberaggressors display a lack of empathy, and a dependence on technologies and truancy [24]; in a high percentage of the cases, the perpetrator was known by the victim [25]; and individuals with disabilities were particularly at risk for cyberbullying [26].…”
Section: Cybervictimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Victims of bullying are found to internalize their problems, they tend to have poor social skills, a tendency to isolate themselves [18], have low self-esteem, frustration, suicidal thoughts [17,[20][21][22], and report greater defenselessness [23]. According to different studies, cyberaggressors display a lack of empathy, and a dependence on technologies and truancy [24]; in a high percentage of the cases, the perpetrator was known by the victim [25]; and individuals with disabilities were particularly at risk for cyberbullying [26].…”
Section: Cybervictimizationmentioning
confidence: 99%
“…In this day and age, when students consume more content online and have the majority of their social and academic interactions on these online media, regulating online activity is of utmost importance. There has been a noticeable increase in the factors affecting cyberbullying susceptibility during the COVID-19 pandemic as a result of an increase in social media and online gaming activity [25]. There is a set of school, social, cultural, and personal variables that can prevent or develop bullying behavior.…”
Section: Emotional Intelligence (Ei) Education and Academic Performmentioning
confidence: 99%
“…As of January 2020, the estimated number of active SM users worldwide was 3.8 billion, reflecting an increase from the number of 3.4 billion in January 2019 [3]. In particular, during the coronavirus disease 2019 (COVID-19) pandemic, there has been an increase in the number of digital platform users [4]. Individuals are now actively posting their new achievements during the pandemic lockdown and expressing their opinions more vocally than before, as SM is now the most frequently used communication method for most individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, during the coronavirus disease 2019 (COVID-19) pandemic, there has been an increase in the number of digital platform users [4]. Individuals are now actively posting their new achievements during the pandemic lockdown and expressing their opinions more vocally than before, as SM is now the most frequently used communication method for most individuals [4]. One study showed that as SM use increases, students who are prone to bullying are more likely to face cyberbullying [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to many studies, the risks of being exposed to cybercrimes have increased due to the Covid-19 pandemic (Jain et al 2020 ; Medina et al 2020 ). Therefore, the urgency of having well defined policies to protect the children has increased as well (Kozma and Isaacs 2011 ; Redmond et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%